Alzheimer's disease - Check, William A. (New York : Chelsea House Publishers, 1989)
Examines the effects, possible causes, diagnosis, and treatment of Alzheimer's disease and problems faced by families of the victims.
Includes index.
Bibliography: p. 90-91.
Booklist.
School Library Journal.
Wilson's Junior High School.
7.8
Keywords: Alzheimer's disease -- Juvenile literature; Alzheimer's disease; Alzheimer's disease